Pengembangan Sistem Informasi Manajemen Dalam Pengelolaan Barang Daerah (Studi Pada Badan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Blitar) - Ramadhani, Sheylla Anugrah (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2015)
Abstract: Development Management Information Sistem to Manage Local Goods (Studies in the Departement of Managerial and Financial Public Goods Kabupaten Blitar).The results showed that the planning of the development management information sistems in the management local goods of Blitar regency from electronic to manual is not performing well. This is because of the requirement in the development of management information sistems in the management of local goods is not sufficient that there are no special rooms as well as laptops and printers are less support for the development of such sistems. AfterÂ that, in the development of management information sistem using a design that is used to facilitate the management of the localgoodsare logged in, parameters, entry and reports are presented in a menuÂ SIMBADA. Then in terms of the implementation of the development of this sistem is still a lot going on one